3tx + 6t + 3hx +6h = 3(tx + 2t +hx +2h) = 3[t(x + 2) + h(x + 2)] = 3(x + 2)(t + h)
Oh, dude, that's like a lot of x's and t's and some random letters thrown in there. So, technically, if you add all the x's, you get 7x, add all the t's, you get 3t, and the random letters are just there for decoration, I guess. So, the sum of x plus x plus x plus x plus x plus x plus x plus t plus t plus t plus jjakw is 7x + 3t + jjakw.
x2 is the same as x times x. In this case x = t+2 so we can say (t+2)2 is (t+2)(t+2) or t2+4t+4
What is the variable of x plus 10 plus 4x-35?
-2x^2 + 17x - 35 = 0 = (-2x + 7)(x - 5) x =7/2 or 5
43 greater than x - 43+x 43 greater than x plus 35 - 43+x+35 43+35+x=78+x
The answer is 9.
The expression (x+5)(x-7) = x^2 -2x -35
(t+h)(x+2)
(x + 2)(h + t)
X2 + 2X - 35 What two factors of - 35 add up to 2? (X - 5)(X + 7) -----------------
If you mean x^2 -12x+35 then it is a quadratic expression which can be factored in the form of (x-7)(x-5)